2003
DOI: 10.1016/j.ydbio.2003.07.019
|View full text |Cite
|
Sign up to set email alerts
|

Distinct octopamine cell population residing in the CNS abdominal ganglion controls ovulation in Drosophila melanogaster

Abstract: Octopamine is an important neuroactive substance that modulates several physiological functions and behaviors of invertebrate species. Its biosynthesis involves two steps, one of which is catalyzed by Tyramine beta-hydroxylase enzyme (TBH). The Tbetah gene has been previously cloned from Drosophila melanogaster, and null mutations have been generated resulting in octopamine-less flies that show profound female sterility. Here, I show that ovulation process is defective in the mutant females resulting in blocka… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
182
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 186 publications
(195 citation statements)
references
References 43 publications
12
182
1
Order By: Relevance
“…We developed GAL4 drivers for each gene and examined their in vivo expression patterns by using two different UAS-GFP reporter lines: UAS-CD8-GFP, a marker reported to be highly concentrated in neural processes including axons and dendrites (24), and UAS-GFP.nls, which contains a nuclear localization signal. Previous studies have detected octopamine and TBH in distinct clusters of cells throughout the central brain and along the ventral midline of the adult thoracic nerve cord (12,25), and recent studies indicate that TBH-expressing neurons send projections through the abdominal ganglion to the female reproductive tract, where they innervate the ovaries and oviduct (12). Based on these results and our real time PCR evidence, we predicted that dTdc2 would be expressed in a similar pattern as that seen for TBH and octopamine.…”
Section: Ro54supporting
confidence: 73%
See 2 more Smart Citations
“…We developed GAL4 drivers for each gene and examined their in vivo expression patterns by using two different UAS-GFP reporter lines: UAS-CD8-GFP, a marker reported to be highly concentrated in neural processes including axons and dendrites (24), and UAS-GFP.nls, which contains a nuclear localization signal. Previous studies have detected octopamine and TBH in distinct clusters of cells throughout the central brain and along the ventral midline of the adult thoracic nerve cord (12,25), and recent studies indicate that TBH-expressing neurons send projections through the abdominal ganglion to the female reproductive tract, where they innervate the ovaries and oviduct (12). Based on these results and our real time PCR evidence, we predicted that dTdc2 would be expressed in a similar pattern as that seen for TBH and octopamine.…”
Section: Ro54supporting
confidence: 73%
“…These cells could either be tyramine-specific neurons or an artifact of the GAL4 driver. As described for TBH (12), dTdc2-GAL4 neurons are located along the ventral midline of the abdominal segment of the thoracic CNS and send axons into the abdominal nerve, where they project over the posterior region of the ovaries and provide heavy innervation to the calyx and to the lateral and common oviducts (Fig. 4, B-D).…”
Section: Ro54mentioning
confidence: 88%
See 1 more Smart Citation
“…In studies on Drosophila ovulation, female postmating behavior, and male courtship or reproductive behavior (Hasemeyer et al, 2009;Lee et al, 2001;Monastirioti, 2003;Yang et al, 2009), abdominal peripheral neurons were observed to directly project to the abdominal ganglion to mediate diverse functions. Therefore, although it is not yet clear what functions the Grs are mediating in the multidendritic neurons and reproductive organs, it seems likely that the information sensed by the Grs in these organs is conveyed to the abdominal ganglion to be processed.…”
Section: Discussionmentioning
confidence: 99%
“…This follicle rupture also relies on proteolytic enzymes, like matrix metalloproteinase 2 (Mmp2), which is specifically expressed in the posterior follicle cells of stage-14 egg chambers (9). Mmp2 activation is stimulated by the monoamine octopamine (OA), which is equivalent to norepinephrine in mammals and is essential for ovulation (10,11). OA binds to its receptor Octopamine receptor in mushroom body (Oamb) in mature follicle cells to induce an intracellular calcium rise, Mmp2 activation, and follicle rupture (12).…”
mentioning
confidence: 99%